Bridging the gap: Gender-sensitive climate information and its implications for cowpea production in Mali - Amos Mensah; Prince Asiedu (Climate Services)
The intersection of gender dynamics and climate information sources significantly shapes the resilience and adaptive capacities of cowpea farmers in Cinzana, Mali. The paper investigates farmers’ access to and perception of climate information, focusing on gender differences that are needed to enhance adaptation to climate variability. The study also explores the constraints faced by both groups in adopting climate-resilient practices. Using data from 260 smallholder cowpea farmers, including 133 men and 127 women, ordered logit and multiple regression models were employed. The results indicate that age, sex, years of experience, and use of high-yielding varieties influence farmers’ frequency of information access from respective sources. The study further revealed that access of information from television, the use of high-yielding varieties, among others, significantly influence cowpea yields. We recommend the promotion of gender-responsive climate information services that facilitate targeted interventions that recognize farmers’ differences to enhance equitable access to resources, improve adaptation, and increase cowpea productivity in Mali.